1997
DOI: 10.1039/a606820k
|View full text |Cite
|
Sign up to set email alerts
|

Ring strain energy and enthalpy of formation of oxiranone: an ab initio theoretical determination

Abstract: The enthalpy of formation ∆H o f,298 for oxiranone is estimated as Ϫ190 ± 10 kJ mol Ϫ1 by means of ab initio molecular orbital calculations at the QCISD(T)᎐ ᎐ full/6-311G(2df,p)//MP2᎐ ᎐ full/6-311G(d,p) level of theory, corresponding to a conventional ring strain energy of 169 kJ mol Ϫ1 . The QCISD(T) calculated enthalpy of formation of cyclopropanone is 6.3 kJ mol Ϫ1 . The oxiranone ring is probably slightly less strained than the cyclopropanone ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…An E2C mechanism with bromide ions acting as a weak base is more likely to be operative . Alternatively, an intramolecular carboxylic acid‐assisted E1‐type elimination pathway involving a hypothetical oxiranone intermediate has also been proposed …”
Section: Methodsmentioning
confidence: 99%
“…An E2C mechanism with bromide ions acting as a weak base is more likely to be operative . Alternatively, an intramolecular carboxylic acid‐assisted E1‐type elimination pathway involving a hypothetical oxiranone intermediate has also been proposed …”
Section: Methodsmentioning
confidence: 99%
“…Wiberg et al [19], through measurements of the enthalpies of combustion, estimated strain energy for methylenecyclopropane about 56 kJ mol -1 greater than that for cyclopropane. Rodriquez et al [20] estimated that cyclopropanone is about 66 kJ mol -1 more strained than cyclopropane and calculated oxirane-2-one to have a ring strain energy 55 kJ mol -1 greater than that of oxirane (ethylene oxide). Turning to endocyclic double bonds, Johnson and Borden [17] and Wiberg et al [19] suggested the strain energy of cyclopropene is ca.…”
Section: Introductionmentioning
confidence: 98%
“…In the first one the three-membered α-lactone ring is formed (reaction 5) and consumed instantly due to its high ring strain (169 kJ·mol -1 from ab initio molecular orbital calculations). 15 Thus in real systems it can exists only at extremely low concentration. 16,17 However, as it was shown by Monte Carlo modelling, this reaction also explains some aspects of the process kinetics.…”
mentioning
confidence: 99%